Implementation of Sunan Kalijaga Dolanan Song Against Children Character Education - Nurul Atsna Qonita; Citra Sonia; Nurul Embun Isnawati; Urfun Nadhiroh; Sania Rahmatika; Ahmad Fauzan Hidayatullah (IAIN Bengkulu, 2020)
This study aims to examine the relationship between the meaning of the song dolirlirilir and sluku-slukubathok with the planting of children’s characters. The dolanan song is a creation of SunanKalijaga as one of his da’wah methods. The method used in this study is a qualitative method with a hermeneutic approach to literature, namely the Hermeneutic Schleiermacher theory. The data analysis technique is in the form of literature study from various sources. Results and discussion Sunan Kalijaga was one of the walisongo who was influential in the process of islamizationin Java. Javanese people who originally still adhered to the beliefs of their ancestors namely Hindu-Buddhist beliefs were not merely willing to convert to Islam, but with the method carried out by Sunan Kalijaga namely cultural and educational approaches can attract the attention of the Javanese people little by little. One method of propaganda sunankalijaga is the creation of dolanan songs which contain moral values that can be used in the cultivation of character in children. Human character is not necessarily obtained from birth but can be shaped by theenvironment.